The Acts of the Apostles: A Socio-Rhetorical Commentary - Pathrapankal, Joseph (Journal of Dharma, 2001)
Ben Witherington 111, The Acts of the Apostles: A Socio-Rhetorical Commentary, Michigan/Cambridge: William B. Eerdmans Publishing Company, Grand Rapids, 1998; pp. xlviii+875, Paperback, 50.00.